Effleurage Technical Applications As The Management Of Pain Labor In Bidan Praktik Mandiri Tembalang District - Wulandari, Dyah Ayu; Putri, Vita Triani Adhi (Health Notions, 2017)
Childbirth is the process of getting the baby out with the contractions of the mothers uterus (Depkes RI,2007). One of the most effective methods used to reduce labor pain is with massage which is one of the nonpharmacological methods performed to reduce labor pain. Midwives have an enormous stake in reducing nonpharmacological pain. Interventions included in the nonpharmacology approach are psychological analgesia performed since early pregnancy, relaxation, massage, kuteneus stimulation, aroma therapy, hypnosis, acupuncture and yoga (Gadysa, 2009). The purpose of this study was to determine the effectiveness of effleurage techniques in reducing labor pain in maternal mothers at Bidan Praktik Mandiri Tembalang District. This research is a quasi-experimental research of pre-post test with control group design (Arikunto, 2009). The subject of this research is 30 maternal mother in Tembalang District selected by purposive sampling technique. Data were collecting using checklist. The analysis used T Test. The result showed there was effect of massage effleurage on the decrease of labor pain at Bidan Praktik Mandiri Tembalang District.